You've been trumped - Baxter, Anthony; Phinney, Richard; Trump, Donald, 1946- (Bullfrog Films, 2012)
In this David and Goliath story for the 21st century, a group of proud Scottish homeowners take on a celebrity tycoon. At stake is one of Britain's very last stretches of wilderness. American billionaire Donald Trump has bought up hundreds of acres on the northeast coast of Scotland, best known to movie-lovers as the setting for the 1983 classic film Local Hero. And like the American oil tycoon played by Burt Lancaster, he needs to buy out a few more locals to make the deal come true. In a land swimming with golf courses, Trump is going to build two more -- alongside a 450-room hotel and 1,500 luxury homes. The trouble is, the land he has purchased occupies one of Europe's most environmentally sensitive stretches of coast, described by one leading scientist as Scotland's Amazon rain forest. And the handful of local residents don't want it destroyed."--Container.